2004
DOI: 10.1080/01443610310001620323
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a gonadotrophin-releasing hormone analogue as first-line management in cyclical pelvic pain

Abstract: One of the most common gynaecological causes of chronic pelvic pain is endometriosis. A lack of correlation between laparoscopic findings and pelvic pain has been reported. As endometriotic lesions are under hormonal influence, the effects of the gonadotrophin-releasing hormone (GnRH) analogues cause shrinkage of the deposits, reducing symptoms caused by them. We carried out a longitudinal, interventional pilot study, examining the effect of leuprorelin acetate 3.75 mg (Prostap SR, Wyeth) on pelvic pain prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…However, studies from USA found 39% (Howard 2000), South Africa 40% (Newham et al 1996) and the UK 42% (Okaro et al 2006), which were closer to the percentage of the normal pelvis found in our study. A 5-year outcome of diagnostic laparoscopy for pelvic pain from Leeds in 2004 found 55% normal pelvis, which was also found in our study (Baxter et al 2004).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, studies from USA found 39% (Howard 2000), South Africa 40% (Newham et al 1996) and the UK 42% (Okaro et al 2006), which were closer to the percentage of the normal pelvis found in our study. A 5-year outcome of diagnostic laparoscopy for pelvic pain from Leeds in 2004 found 55% normal pelvis, which was also found in our study (Baxter et al 2004).…”
Section: Discussionsupporting
confidence: 79%
“…This has been reiterated by an expert panel of practicing gynaecologists from all over the USA, stating that laparoscopic confirmation of the diagnosis is unnecessary, and a trial of medical therapy is justified, provided that there are no other indications for surgery such as the presence of a suspicious adnexal mass (Gambone et al 2002). A study in the UK discussed the value of first-line GnRH analogues in a small number of patients with cyclical pelvic pain (Baxter et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…supports the notion that specific medical therapy should always follow, or even precede any surgical procedure, as a first-line treatment, given the high success rate in relieving pain symptoms (13,14). This view would be corroborated by the poor correlation between the intensity of pain and the revised AFS stage, and the evidence that endometriosis could often be microscopic in extension (15).…”
mentioning
confidence: 82%
“…Several studies have shown the efficacy of currently available hormonal treatments in alleviating pain symptoms in women with endometriosis (16,17). However, no study has investigated yet whether hormonal treatment changes nerve fiber density in endometrium and myometrium in women with endometriosis who have pain symptoms.…”
mentioning
confidence: 98%